An Analysis of Technology Issues in Mobile Augmented Reality - Pinandita, Tito; Mahfuzah Mohamad, Siti Nurul; Nadia Azman, Farah; Himawan, Hidayatulah (Informatica, 2023)
Augmented reality technology is now increasingly modern and developing rapidly, this research is a summary of the popularity of augmented reality technology to date. Augmented reality applications are increasingly used in the fields of education, health, and even the military. Other research explains how to combine augmented reality with other technologies. By conducting a literature review of 1582 documents from 2017 to 2022 related to augmented reality, several combinations using AR technology were obtained. This research is to find challenges and opportunities for augmented reality applications in the future. Some studies illustrate that there are still some shortcomings in augmented reality technology, either in the form of image quality or the design of the technology. It is expected that in the future, the shortcomings found in previous studies can be improved.